Microscopic Isthmuses and Fibrosis Within the Border Zone of Infarcted Hearts Promote Calcium-Mediated Ectopy and Conduction Block - Campos, Fernando O.; Shiferaw, Yohannes; Weber dos Santos, Rodrigo; Plank, Gernot; Bishop, Martin J. (Frontiers in Physics, 2018)
Ventricular tachycardia (VT) secondary to myocardial infarction (MI) remain a major cause of sudden death in adults. Premature ventricular complexes (PVCs), the first initiating beats of a portion of these arrhythmias, arise from triggered activity in the infarct border zone (BZ). At the cellular scale, spontaneous calcium release (SCR) events are a known cause of triggered activity and have been reported in cells that survive MI. At the tissue scale, fibrosis has been shown to play an important role in creating the substrate for VT. However, the interplay between SCR-mediated triggered activity and fibrosis upon VT formation in infarcted hearts has not been fully investigated. Here, we conduct in-silico experiments to assess how macroscopic and microscopic anatomical properties of the BZ can create a substrate for SCR-mediated VT formation. To study this question, we employ a stochastic subcellular-scale model of SCR events and action potential to simulate different cardiac preparations. Within 2D sheet models with idealized infarct scars and BZ we show that the probability of PVCs is higher, 55%, in preparations with thin conducting isthmuses (0.2 mm) transcending the scar. In an anatomically-detailed model of the rabbit ventricles with a realistic representation of intramural scars, we show that the heart’s protective source-sink mismatch prevents ectopy. Furthermore, we demonstrate that fibrosis disrupts this antiarrhythmic mechanism making PVCs more likely. PVC probability is highest (≥ 25%) when fibrosis accounts for 60% and 90% of the BZ in the 2D sheet and the 3D anatomical model, respectively. Above these thresholds, PVC occurrence decreases because of: 1) the reduced number of myocytes in the BZ; 2) conduction block. Block is caused either by disconnection of BZ cells from the myocardium or due to source-sink mismatches at regions of rapid tissue expansion. Moreover, while outward propagation to healthy tissue may fail, PVCs traveling inward through the scar might encounter more favorable loading conditions. These PVCs may exit to the myocardium and reenter back at the region of block. Overall, our findings indicate that thin isthmuses and strands of myocytes interspersed with fibrosis can be arrhythmogenic. Ablation of these microscopic structures may prevent VT formation.